SEKOLAH DAN PENDIDIKAN AGAMA KATOLIK DALAM MASYARAKAT PLURAL: MEMBANGUN DIALOG DAN MENANGKAL RADIKALISME - Fransiska Widyawati (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
This article is motivated by the concern of the phenomenon of religious-based intolerance and radicalism in Indonesia. Perpetrators of these attitudes and behaviors occur in many educational settings by educated individuals. There have been cases where radicalism happens because schools are developing religious education, which is exclusive and not open to pluralism in society. Therefore, this article develops ideas/thoughts about schools and Catholic Religious Education (CRE) relevant in the context of pluralism in Indonesia to prevent religious intolerance and radicalism. Schools can be pluralism-friendly homes by making them a positive space for diversity and a place for humanist dialogical education. In Indonesian pluralism, Catholic Religious Education helps students know their religious faith and get to know other religions, have a dialogue with the truths of other religions, and even learn from other religions. PAK in the Indonesian context must contribute to building the personality and attitude of students who are inclusive, dialogical, humanist, and fair. CRE should not be used as an apologetic tool for the sake of defending the truth of Catholicism narrowly and exclusively. Through CRE, students are helped to become individuals and Indonesians who are tolerant, fair, and dignified